Penentuan Keuntungan Maksimum Usaha Catering di Kota Samarinda - Aswin Adi Pratama; Sjamsu Djohan; Nur Janana (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Determination of the maximum profit catering business in Samarinda City. Guidance Mr. Sjamsu Djohan and Mrs. Nurjanana.This research aims to find out whether advantages gained of catering business in Samarinda City had already reached the maximum profit. The research of using primary data obtained from observations and interviews in person and there are 7 samples taken from various businesses catering, analyzed by using the formula of maximum profit and use the analysis tool Multiple Linear Regression. Hypothesis testing using t-test or a different test and analyzed quantitatively using a computer program SPSS (statistical package for the social science) 23.00. The results of this research show that the catering business in the Samarinda City have profit but gains haven't reached the maximum. The hypothesis proposed that the catering business in the Samarinda City has achieved maximum advantage was rejected because the maximum output is not the same as the average output.